PATTERN OF DYSLIPIDEMIA IN ADULT DIABETIC SUBJECTS IN THE COMMUNITY HOSPITAL OF DISTRICT SWAT - Jan, Sahibzada Saeed; Khan, Taj Muhammad; Ahmad, Rashid; Zaman, Safeer; Ahmad, Aziz (Journal of Ayub Medical College Abbottabad, 2011)
Background: The incidence of diabetes is growing at dramatic rates around the word and its complications are associated with significant health and financial burdens, warranting strong and comprehensive prevention efforts. The objective of the present study was to evaluate the pattern of dyslipidemia in the adult diabetic patients in Saidu Teaching Hospital, Saidu Sharif, Swat. Methods: The study comprised of 100 subjects, 50 subjects with diabetes and 50 (non-diabetic) controls. The serum Cholesterol, Triglycerides, High-density Lipoprotein-Cholesterol (HDL-C) and Low-density Lipoprotein-Cholesterol (LDL-C), blood sugar (random and fasting), blood pressure (systolic and diastolic) of Diabetic subjects were compared with Control subjects. Results: Diabetic subjects had high mean value of Triglycerides and LDL-C (but statistically nonsignificant), low level of HDL-C (statistically highly significant) and high blood pressure as compared to Control subjects. Conclusion: Dyslipidemia is a potent predictor of cardiovascular morbidity and mortality in diabetic patients. Keywords: Diabetes mellitus, Dyslipidemia, Blood pressure